Electoral law and its features in Kazakhstan as part of the Russian empire in the late XIX-early XX century - Kozhakhmetov, G.Z.; Botagarin, R.B. (Bulletin of the Karaganda University “Law Series”, 2018)
This scientific article is devoted to the formation of electoral law in the Steppe and Turkestan region during the period of their entry into the Russian empire. The article reveals that the autocratic regime of tsarist Russia was one of the rigid political systems, which did not have representative bodies of power with legislative powers. Thanks to the revolution of 1905 and the establishment of the first Russian Parliament – the state Duma in the Russian empire and its national suburbs was formed the right to vote. The authors show that the electoral right was unequal, class, multi-stage, in addition, some categories of the population were generally forbidden to participate in elections, they were: women, students, soldiers, persons under 25 years of age and «vagrant foreigners». It is revealed that tsarism in its electoral legislation divided the population into alien and indigenous, and among the newcomers, i.e. immigrants, preferred the Cossacks, which was a strong stronghold of tsarism in carrying out its colonial policy in the national suburbs. At the same time, the authors point out that the elections for the first time opened up unprecedented opportunities for the colonial peoples of Russia to participate in the Duma elections. Based on archival materials, the authors showed that the election campaigns conducted in the early twentieth century raised to a new level the social and ideological life of Kazakhstan and contributed to the growth of national consciousness in the struggle for their civil rights and political freedoms.